Two-year study of lipophilic marine toxin profile in mussels of the North-central Adriatic Sea: First report of azaspiracids in Mediterranean seafood. (15th December 2015) - Bacchiocchi, Simone; Siracusa, Melania; Ruzzi, Angela; Gorbi, Stefania; Ercolessi, Manuela; Cosentino, Maria Anna; Ammazzalorso, Patrizia; Orletti, Roberta
Abstract: Since the late 1980s, the North-central Adriatic Sea has frequently experienced blooms of harmful algal species, producing marine lipophilic toxins (MLTs) which accumulate in mussels and pose a serious threat to consumer health. Here, we present a 2-year LC-MS/MS study (2012–2014) of the MLT profile in mussels from the North-central Adriatic Sea in the context of the presence of toxic phytoplankton concentrations in seawater. Okadaic acid increased in mussels from all areas during the summer and autumn-winter periods with a rising trend between 2012 and 2014. In the same periods, Dinophysis sp. increased in abundance in seawater, but the highest densities of algae did not always coincide with the highest levels of toxins in mussels. Yessotoxins (YTXs) content in mussel increased sharply in the autumn-winter periods even exceeding the legal limit; although this accumulation did not always correlated with the YTX-producers in water (such as Lingulodinium polyedrum and Protoceratium reticulatum ) a massive bloom of Gonyaulax spinifera was reported in November 2013, suggesting the role of this species in YTXs shellfish contamination. Traces of Azaspiracid 2 (AZA-2) were observed often in mussels during the study period, confirming for the first time the presence of this biotoxin in Mediterranean seafood. Highlights: We report a 2-years long study of marine lipophilic toxins in mussels of North central Adriatic Sea. Okadaic acid and yessotoxins were largely predominant in the toxin profile of molluscs. Yessotoxins caused problems to local mussel growers since autumn until the late winter. Traces of AZA-2 were observed for the first time in Mediterranean seafood.